No Child Left Behind’s Implementation in Urban School Settings: Implications for Serving Students with Emotional and Behavior Disorders - Fitzpatrick, Michael; Knowlton, Earle (Journal of the American Academy of Special Education Professionals, 2007)
The No Child Left Behind Act (NCLB, 2002) has generated controversy and support since its inception. Parents, teachers, researchers, authors, advocates, protesters, and politicians have shared views and opinions based on "political" beliefs, biases, and anecdotal and research-based evidence that supports their stance. In attempt to sidestep political attacks or endorsements of NCLB, we reviewed the literature regarding NCLB’s basic principles, its issues in urban school settings, and its impact on students identified as emotionally and behaviorally disturbed who receive special education services in urban school settings. We also discussed relevant recommendations, methods, and strategies to increase a school’s capacity and student outcomes.